Commodity Variation Test with Seed Chip Molder - Rizki Aminullah Lubis; Saipul Bahri Daulay; Lukman Adlin Harahap (Universitas Sumatera Utara, 2016)
One of agricultural mechanization excellence is to improve agricultural product value compered to the row one. Beside melinjo that has been popular to become chip, cempedak’s seed, jackfruit’s seed, and durian’s seed else can be processed to be come chip. This research was aimed at testing the effective commodity types on chip’s maker machine. Therefore, a research had been conducted at Agricultural Engineering Laboratory, Faculty of Agriculture USU in February 2015 until March 2015 using cempedak seed, durian seed and jackfruit seed. Parameters observed were effective capacity on and organoleptic test. The results showed that the best capacity using durian seeds i.e 14,44 kg/hour. Keywords: Seed Chip Molder, cempedak seeds, durian seeds and jackfruit seeds.